Characterization of La0.6Sr0.4CoO3-α cathode powder prepared by a combined citrate-EDTA method / Abdullah Abdul Samat, Mohd Azlan Mohd Ishak and Nafisah Osman - Abdul Samat, Abdullah; Mohd Ishak, Mohd Azlan; Osman, Nafisah (Universiti Teknologi MARA, Perlis, 2012)
The La0.6Sr0.4CoO3-α (LSCO) cathode powder was prepared by a combined citrate-EDTA method using nitrate based chemicals. Citric (CA) and ethylenediaminetetraacetic acid (EDTA) were used as chelating agents and ethylene glycol (EG) as a polymerizing agent. The formation of metal complexes of LSCO was analyzed using Fourier transform infrared (FTIR) spectroscopy. Various organic compounds such as carbonyl and carbonate groups were observed in FTIR spectra. The as-synthesized LSCO powder analyzed by thermogravimetric analysis (TGA) showed there were three stages of weight losses with a drastic weight loss observed between 150-550 ºC. A complete decomposition of intermediate compounds was observed at 800 ºC indicating the formation of metal oxide was formed. This result was further confirmed by X-ray diffraction (XRD) analysis which revealed the calcined LSCO powders at 800 ºC and 900 C formed a single perovskite phase. LSCO cathode slurry was prepared by adding polyvinyl pyrrolidone (PVP) as binder. This slurry was painted on pellet surfaces of BaCe0.54Zr0.36Y0.1O2.95 (BCZY) electrolyte. Scanning electron microscopy (SEM) results showed the LSCO cathode was well adhered on BCZY electrolyte. It is apparent that the binder plays an important role in making a good contact between the obtained high purity LSCO cathode and BCZY electrolyte.